Interactions between almond plantations and native ecosystems: Lessons learned from north‐western Victoria. (January 2014) - Luck, Gary W.; Spooner, Peter G.; Watson, David M.; Watson, Simon J.; Saunders, Manu E.
<x xml:space="preserve">Abstract</x> Five years of research on interrelationships between fauna use of almond plantations and native vegetation in north‐western Victoria shows that almond plantations have a strong influence on fauna dynamics and in some cases may provide important habitat for threatened species.